Предмет: Алгебра,
автор: NastyaKityuk
Разложи на множители (x+24y)^2-(24x+y)^2
Ответы
Автор ответа:
0
Решение
(x+24y)² - (24x+y)² = (x + 24y - 24x - y)*(x + 24y + 24x + y) =
= (- 23x + 23y)*(25x + 25y) = - 23*25*(x - y)*(x + y) =
= - 575*(x - y)*(x + y)
(x+24y)² - (24x+y)² = (x + 24y - 24x - y)*(x + 24y + 24x + y) =
= (- 23x + 23y)*(25x + 25y) = - 23*25*(x - y)*(x + y) =
= - 575*(x - y)*(x + y)
Автор ответа:
0
Спасибо огромное
Похожие вопросы
Предмет: Қазақ тiлi,
автор: nekkkii
Предмет: Физика,
автор: Аноним
Предмет: Русский язык,
автор: mashasudina
Предмет: Химия,
автор: kundizsaparbaev
Предмет: Алгебра,
автор: marzhanmaratov